القيمة الإنذارية لل CD25 عند مرضى الابيضاض النقوي الحاد - حسين فراس; الشمالي سوزان; أحمد علا (Latakia University Journal -Medical Sciences Series, 2019)
Background: Acute myeloid leukemia (AML) is a heterogeneous hematologic malignancy characterized by a clonal expansion of myeloid blasts. Treatment strategies of patients with AML are based on various prognostic factors, including age and performance status of the patient , as well as cytogenetic and molecular characteristics of the leukemic clone . Aim : Studying the expression of cluster of differentiation (CD) 25 in adult patients with newly diagnosed AML and to assess its prognostic relevance . Materials and Methods : This study was conducted on 55 newly diagnosed AML patients at the Hematology Unit , Internal Medicine Department , Tishreen University Hospital . All patients were subjected to full history taking, thorough clinical examination , and laboratory investigations , including detection of CD25 expression on blast cells by flow cytometry. Results : In our study group , 12 patients (21.8%) were positive for CD25 expression , using univariate and multivariate analyses we demonstrated that high pretreatment CD25 expression (≥20%) on leukemic blasts was associated with significantly worse response to first induction therapy and significantly decreased overall and relapse free survival rates of AML patients subjected to standard induction chemotherapy. Conclusion : Expression of CD25 in AML patients at presentation can be considered a poor independent prognostic factor . الخلفية: الابيضاض النقوي الحاد (AML) هو خباثة دموية غير متجانسة تتميّز بتكاثر نسيليّ واسع للأرومات النقوية. تعتمد الاستراتيجيات العلاجية لمرضى AML على العديد من العوامل الإنذارية و الحالة الأدائية للمريض و كذلك على الخصائص الجزيئية و الجينية للنسيلة الابيضاضية . الهدف : دراسة التعبير عن CD25 لدى المرضى البالغين المشخصين حديثاً بالابيضاض النقوي الحاد و تقييمه دوره الإنذاري . المواد و الطرق : شملت هذه الدراسة 55 مريض AML مشخص حديثاً في شعبة أمراض الدم , قسم الأمراض الباطنة, مشفى تشرين الجامعي . خضع جميع المرضى لأخذ قصة مرضية , فحص سريري, و استقصاءات مخبرية شملت الكشف عن التعبير عن CD25 على الأرومات عبر إجراء flow cytometry . النتائج : في دراستنا , امتلك 12 مريض (21.8%) تعبيراً إيجابياً عن CD25 , باستخدام التحليل أحادي المتغيرات (univariate) و التحليل متعدّد المتغيرات (multivariate) وجدنا أنّ التعبير المرتفع عن CD25 (≥ 20%) على الأرومات الابيضاضية قبل العلاج يترافق مع استجابةٍ أسوأ على الشوط الهجومي الأوّل (induction) و كذلك مع بقيا كلية (OS) أسوأ و بقيا خالية من النكس (RFS) أقصر عند مرضى AML المعالجين بالعلاج الكيميائي المعياري . الخلاصة : يمكن اعتبار التعبير عن CD25 لدى مرضى الابيضاض النقوي الحاد عند التظاهر عاملاً إنذارياً سيئاً مستقلاً .